Ответы и объяснения

Лучший Ответ!
2012-02-15T18:38:37+00:00

2(3Cosx+Cos3x/4)=2SinxCosx

 3Cosx+Cos3x/4=SinxCosx

  3Cosx+Cos3x=4SinxCosx

3Cosx + 4Cos^3(x) - 3 Cosx -4SinxCosx=0

4Cos^3(x)-4SinxCosx=0

Cos^3(x)-SinxCosx=0

Cosx(Cos^2x-Sinx)=0

Cosx=0                         Cos^2(x)-Sinx=0

x=п/2+пn,nэz                1+Cos2x/2 - Sinx=0

                                    1+Cos2x-2Sinx=0

                                    1+1-2Sin^2(x)-2Sinx=0

                                    2Sin^2(x)+2Sinx-2=0

                                    Sin^2(x)+Sinx-1=0

                                   нет решения

=> ответ: x=  п/2+пn,nэz